Recursos didácticos de Mmaría Montessori para el desarrollo sensorial de niños de 3 a 4 años - Chiluisa Guayasamin, Katherine Johanna (2022)
The research carried out on the Basic Principles of the Montessori Method in Early Education at the "Marco Aurelio Subía Martínez - Batalla de Panupali" Educational Unit, is based on a mixed approach, which is aimed at determining the level of applicability of the Montessori method, For this purpose, techniques and instruments were elaborated where it was observed that in the surveys made to authorities and teachers, there is a wide percentage favorable to imparting the methodology in the classroom, since its principles help to develop cognitive skills, covering all the affective, physical and speech areas that will allow the infant to respect his learning pace. The proposal had the objective of designing a guide on didactic resources and prepared environments, based on the constructivist approach of the Montessori method, through playful activities for children's progress that will allow sensory development in children from 3 to 4 years old, in order to strengthen autonomy, through the proper use of prepared environments and didactic material, taking into account the application in the classroom, emphasizing in an essential way the game, since it is fundamental for their process. The activities proposed in the guide are relevant because they facilitate several play-work functions that can be taken into account for meaningful learning and guaranteeing the sensory and integral development of the child. This proposal was validated by experts and users of the initial education area, having as a conclusion, that these environments should be implemented, for this reason the author seeks that the infant gets knowledge in an experiential way established in freedom at the time of learning, each activity raised seeks a dynamic teaching where several games with didactic materials are carried out and thus allowing him to develop and define his sensory perceptions.